2014
DOI: 10.1007/s40264-014-0226-z
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Cytokines Approved for Therapy

Abstract: Cytokines, currently known to be more than 130 in number, are small MW (<30 kDa) key signaling proteins that modulate cellular activities in immunity, infection, inflammation and malignancy. Key to understanding their function is recognition of their pleiotropism and often overlapping and functional redundancies. Classified here into 9 main families, most of the 20 approved cytokine preparations (18 different cytokines; 3 pegylated), all in recombinant human (rh) form, are grouped in the hematopoietic growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(118 citation statements)
references
References 242 publications
(227 reference statements)
0
117
0
1
Order By: Relevance
“…Treatment with recombinant leptin therapy through subcutaneous injection produces short-lasting effects and therefore requires repetitive doses. The supra-physiological increase in circulating leptin level following regular injection is associated with serious side effects 37 . Gene therapies with AAV vectors have been attempted in ob/ob mice, an animal model best recapitulating human congenital leptin deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with recombinant leptin therapy through subcutaneous injection produces short-lasting effects and therefore requires repetitive doses. The supra-physiological increase in circulating leptin level following regular injection is associated with serious side effects 37 . Gene therapies with AAV vectors have been attempted in ob/ob mice, an animal model best recapitulating human congenital leptin deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Pleiotropic actions can induce counterbalancing cellular activities, resulting in blunted therapeutic efficacy (Hart et al, 2014; Lin et al, 1995). Furthermore, pleiotropy exacerbates off-target toxicities through activation of undesired cell types (Baldo, 2014; Krieg et al, 2010). Previous studies have shown that natural and engineered ligands, which modulate receptor dimerization by altering receptor-ligand complex stability, affinity and/or geometry, have the capacity to modulate downstream signaling outputs and target cell selectivity (Levin et al, 2014; Macdonald-Obermann and Pike, 2014; Mitra et al, 2015; Moraga et al, 2015a; Moraga et al, 2015b; Riese, 2011; Yea et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy with rhG-CSF is commonly used to mitigate THP-induced granulocytopaenia in the clinic. However, rhG-CSF combination therapy is expensive and associated with multiple side-effects (22). Therefore, new strategies to prevent or reduce the toxicity of chemotherapy at the level of haematopoiesis are essential to improve therapeutic outcome Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…LNT is a β-D-glucan extracted from shiitake mushrooms (Lentinus edodes). A role for LNT in regulating the immune system has been implicated both in vivo and in vitro by several studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Moreover, LNT has antitumour (23), antioxidation (24) and DNA damage repair activities (12).…”
Section: Discussionmentioning
confidence: 99%